Nmr-based metabolomic study of medicinal plants used against malaria and the isolation of bioactive alkaloids - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.